Welding defects at friction stir welding - P. Podržaj (Metalurgija, 2015)
The paper presents an overview of different types of defects at friction stir welding. In order to explain the reasons for their occurrence a short theoretical background of the process is given first. The main emphasis is on the parameters that influence the process. An energy supply based division of defects into three disjoint groups was used. The occurring defects are demonstrated on various materials.